Sugar consumption profiles in mead production using accessible control analysis - Jeferson S. Vitorino-Junior; Maria C.T. Mansano; Lígia B. Alcalde; Samara T. Santos; Gustavo G. Fonseca; Rodrigo S.R. Leite; William R.C. Vega; Marcelo F. da Paz (Kuwait Journal of Science)
The lack of standardized protocols for mead production leads to a degree of unpredictability in the final alcoholic product due to a limited understanding of precursor components' interactions in raw materials. Therefore, this study endeavors to simplify mead production by conforming to Brazilian legislative guidelines through an accessible wort standardization process. To mitigate variability in final products, including grape wine standards, it is necessary to investigate more dependable and accessible analytical methods for small producers. To study this standardization, a 120-day fermentation was carried out with monthly sampling, where sugars were evaluated: glucose, fructose, sucrose, and ethanol, using inexpensive methods. The results showed that most of the alcoholic fermentation takes place in the first 30 days, stabilizing afterwards. It was also clear that glucose has the best correlation with the generation of ethanol above 0.98 and is the most accessible method because, in addition to being found in any pharmacy, it is accurate, cheap, and fast. It has also been shown that there is a higher conversion with a lower concentration of honey in the wort, which is interesting in terms of cost-benefit.